2016
DOI: 10.1186/s13045-016-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib in steroid refractory graft-vs.-host disease: a case report

Abstract: BackgroundAllogeneic hematopoietic stem cell transplantation (HSCT) is potentially curative in a variety of hematological malignancies. Graft-vs.-host disease (GvHD) remains a life-threatening complication. Standard treatment is high-dose (HD) corticosteroids. Steroid-refractory (SR) GvHD is associated with poor prognosis. At present, second-line treatment is ill-defined and includes a number of agents. Novel insights into the pathophysiology of acute GvHD (aGvHD) highlight the relevant role of the host inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…One patient with cGVHD died from a GVHD flare following ruxolitinib discontinuation; the remaining patients were successfully treated with a low maintenance dose of ruxolitinib or slow tapering following response to treatment. Similar findings have been reported in adult patients with aGVHD or cGVHD [35,[42][43][44] and pediatric patients with aGVHD [45]. These data suggest that ruxolitinib provides clinical benefit and durable responses in patients with SR GVHD; however, further data from large prospective clinical trials are required.…”
Section: Overview Of Ruxolitinib and Rationale For Targeting Jak Signalsupporting
confidence: 80%
“…One patient with cGVHD died from a GVHD flare following ruxolitinib discontinuation; the remaining patients were successfully treated with a low maintenance dose of ruxolitinib or slow tapering following response to treatment. Similar findings have been reported in adult patients with aGVHD or cGVHD [35,[42][43][44] and pediatric patients with aGVHD [45]. These data suggest that ruxolitinib provides clinical benefit and durable responses in patients with SR GVHD; however, further data from large prospective clinical trials are required.…”
Section: Overview Of Ruxolitinib and Rationale For Targeting Jak Signalsupporting
confidence: 80%
“…The patient ultimately developed cGVHD 2 months after tapering and discontinuing ruxolitinib. Finally, in a case study, ruxolitinib was associated with complete resolution of grade 2 aGVHD in the gastrointestinal tract and skin after 21 days of treatment, as confirmed by histology (71).…”
Section: Clinical Evidence With Jak1/jak2 Inhibitorsmentioning
confidence: 86%
“…These authors also reported a potent reduction of GVHD symptoms and serum cytokines in six patients with acute and chronic steroid-refractory GVHD [ 133 ]. Maffini et al described a patient with steroid-refractory grade IV acute GVHD treated with ruxolitinib with complete resolution of symptoms [ 134 ]. Additionally, Zeiser et al carried out a retrospective multicenter survey with 95 GVHD steroid-refractory patients treated with ruxolitinib, and showed overall and complete response rates of 81.5 and 46.3%, respectively, for acute GVHD, and 85.4 and 7.3%, respectively, for chronic GVHD [ 135 ].…”
Section: Treatmentmentioning
confidence: 99%